The end of history. Thirty years on - La Torre, Massimo (UNIVERSITAS. Revista de Filosofía, Derecho y Política, 2020)
The fall of the Berlin Wall was hailed by many analysts and academics as the start of a new era. With the end of the Cold War, a new stage of peace and prosperity loomed. After the "liberal revolution", some sighted the "end of history". But such hope quickly dissipated: the disappearance of "real socialism" re-launched rampant capitalism and not only in the countries yesterday under the Soviet orbit. Ordoliberalism understood as the establishment of a highly competitive and jurisdictionally guaranteed economic model also infiltrated the European institutions. The crisis of 2010 confirmed for Europe its neoliberal, technocratic drift. The shock wave of November 9, 1989, has not yet ended. New turmoil waits. Brexit can also be interpreted in this key, as another demolition company, "liquidation", "liberalization".